2015
DOI: 10.2139/ssrn.2551636
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Governance and Firm Performance in Pakistan: The Case of Karachi Stock Exchange (KSE)-30

Abstract: This paper examine the relationship between four important corporate governance mechanisms (board size, board composition, CEO/chairman duality and audit committee) and two firm performance measures (return on equity, ROE, and profit margin, PM), for a sample of 30 Pakistani listed firms between 2008 and 2009. The results provide evidence of a positive significant relationship between ROE and PM and three corporate governance mechanisms (board size, board composition and audit committee). The implication of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
112
2
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 86 publications
(125 citation statements)
references
References 35 publications
8
112
2
3
Order By: Relevance
“…Thus, hypothesis H1b is supported. This finding is consistent with previous studies that found a positive relationship between board size and Tobin`s Q either in developed countries such as Khanchel, 2007;Larmou & Vafeas, 2010;Premuroso & Bhattacharya, 2007;Sueyoshi et al, 2010 or in developing countries like Kang and Kim (2011), Khan and Javid (2011, Kyereboah-Coleman (2007, Kyereboah-Coleman andBiekpe (2006), Ll, Kankpang andOkonkwo (2012), Najjar (2012), Obiyo andLenee (2011), Swamy (2011), Uadiale (2010) and Yasser, Entebang and Mansor (2011). One probable clarification for the positive significant association between board size and Tobin`s is that this result is supported by resource dependence theory, which postulates that the board has to be more strict when it comes to monitoring of management to ensure minimal financial fraud.…”
Section: Regression Results Of Model (Based On Marketing Measure)supporting
confidence: 92%
See 3 more Smart Citations
“…Thus, hypothesis H1b is supported. This finding is consistent with previous studies that found a positive relationship between board size and Tobin`s Q either in developed countries such as Khanchel, 2007;Larmou & Vafeas, 2010;Premuroso & Bhattacharya, 2007;Sueyoshi et al, 2010 or in developing countries like Kang and Kim (2011), Khan and Javid (2011, Kyereboah-Coleman (2007, Kyereboah-Coleman andBiekpe (2006), Ll, Kankpang andOkonkwo (2012), Najjar (2012), Obiyo andLenee (2011), Swamy (2011), Uadiale (2010) and Yasser, Entebang and Mansor (2011). One probable clarification for the positive significant association between board size and Tobin`s is that this result is supported by resource dependence theory, which postulates that the board has to be more strict when it comes to monitoring of management to ensure minimal financial fraud.…”
Section: Regression Results Of Model (Based On Marketing Measure)supporting
confidence: 92%
“…Hence, hypothesis H10 is not supported. The result of this variable is similar to previous studies that revealed positive relationship between them whether in developed countries (Dey, 2008;Khanchel, 2007) or developing countries (Abdullah et al, 2008;Nuryanah& Islam, 2011;Saibaba & Ansari, 2011;Swamy, 2011;Yasser et al, 2011). One explanation for the positive significant relationship between audit committee independence and Tobin`s Q is that this finding is supported by both agency theory and resource dependence theory where autonomy is given to make the right decision without any restriction or condition, to detect errors and to reveal them without any problems because independent reviewers are not related to the company in any way.…”
Section: Regression Results Of Model (Based On Marketing Measure)supporting
confidence: 89%
See 2 more Smart Citations
“…The data used in this study was based on the recent two years 2011 and 2012 like previous studies (Braun & Sharma, 2007;Dey, 2008;Kim & Yoon, 2008;Yasser, Entebang, & Mansor, 2011). The next section is to provide a wide discussion of the relevant literature.…”
Section: Introductionmentioning
confidence: 99%